Investigation of Radiation Effect on Structural and Optical Properties of GaAs under High-Energy Electron Irradiation - Authit Phakkhawan; Aparporn Sakulkalavek; Siritorn Buranurak; Pawinee Klangtakai; Karnwalee Pangza; Nongnuch Jangsawang; Sawinee Nasompag; Mati Horprathum; Suphakan Kijamnajsuk; Sakuntam Sanorpim (Materials, 2022)
A systematic investigation of the changes in structural and optical properties of a semi-insulating GaAs (001) wafer under high-energy electron irradiation is presented in this study. GaAs wafers were exposed to high-energy electron beams under different energies of 10, 15, and 20 MeV for absorbed doses ranging from 0-2.0 MGy. The study showed high-energy electron bombardments caused roughening on the surface of the irradiated GaAs samples. At the maximum delivered energy of 20 MeV electrons, the observed root mean square (RMS) roughness increased from 5.993 (0.0 MGy) to 14.944 nm (2.0 MGy). The increased RMS roughness with radiation doses was consistent with an increased hole size of incident electrons on the GaAs surface from 0.015 (0.5 MGy) to 0.066 nm (2.0 MGy) at 20 MeV electrons. Interestingly, roughness on the surface of irradiated GaAs samples affected an increase in material wettability. The study also observed the changes in bandgap energy of GaAs samples after irradiation with 10, 15, and 20 MeV electrons. The band gap energy was found in the 1.364 to 1.397 eV range, and the observed intense UV-VIS spectra were higher than in non-irradiated samples. The results revealed an increase of light absorption in irradiated GaAs samples to be higher than in original-based samples.
Keywords: Semiconductor materials and devices; Thin-Film Transistor Technologies; Ga2O3 and related materials